IMPROVING THERMAL WITHSTANDING CAPACITY OF THREE PHASE INDUCTION MOTOR USING NWCC METHOD - Khan, Banti; Goyal, Ashita; Kumar Chobey, Ashutosh (International Journal of Research -GRANTHAALAYAH, 2014)
Three phase induction motors are widely used in industries due to their various technical as well as economical advantages. About 60% of industrial electricity is consumed by these motors, but the heat generation inside the motor due to various losses is a critical factor which degrades the dielectric properties of insulation and shortening the lifespan of motor. This paper presents the capillary based water cooling method of three phase squirrel cage induction motor. In this method, a jacket of capillaries made of jute and cotton is used as a outer cover for the motor casing. A small air gap passage is provided in between motor casing and inner surface of jacket. Natural Water Cooling Capillaries (NWCC) method is used to lower down the surrounding temperature of motor which reduces heating limitations of motor. For this purpose we select a 1.1kW three phase, 50Hz squirrel cage induction motor. Heat run test is performed on this motor to determine the total loss of energy dissipated as heat on three phase squirrel cage induction motor with and without adopting capillary based water cooling method. Comparison is done on the basis of experimental result which shows that the temperature withstanding capacity of induction motor will increase by 15.5 % after adopting capillary based water cooling method. This is an economical method and no external energy is required for cooling purpose.